Human immune responses during schistosomiasis mansoni - Giovanni Gazzinelli; Daniel G. Colley (Sociedade Brasileira de Medicina Tropical (SBMT), 1992)
Studies of immune responses as they occur in patients with schistosomiasis appear to progress relative to corrent technological advances, and to advance despite the understandable inability to pursue in vivo manipulations in this host/parasite system. Emphasis is most often placed on making immunological comparisons between such patient groups as reinfected/non-reinfected, intestinals/hepatosplenic, high/low intensities of infection, infected/uninfected within endemic areas, and those born of infected/uninfected mothers. Based on these types of comparisons, reasonable conjectures can be made regarding the immunological occurrences during this chronic exposure condition. Some consideration is now being given to the immune mechanisms of some of the observations made, and while some of these must then be carried back to experimental models for further manipulation-based analysis, new technological developments continue to assist in the field/bench ability to ask questions that might assist our understanding to a point where this knowledge can be applied to shaping developmental approaches to vaccine development and the goal of alleviating morbidity. O estudo da resposta imune de pacientes com esquistossomose progride em função do avanço tecnológico, apesar das dificuldades de manipulação in vivo deste complexo sistema parasita-hospedeiro. A ênfase nos estudos tem sido mais freqüentemente dirigida para comparações entre grupos característicos de indivíduos, tais como infectado/não infectado, reinfectado/ não reinfectado, assintomático/hepato-esplênico, com intensidade de infecção alta/baixa, etc. Baseado nessas comparações tem-se obtido informações que permitem conjecturas razoáveis com relação à regulação imunológica, susceptibilidade e resistência e até mesmo considerações sôbre mecanismos, que têm sido mais apropriadamente analisados, entretanto, em sistemas experimentais. Tais estudos têm como finalidade a compreensão das camas e eventos que le vam à morbidade e ao desenvolvimento de uma vacina humana anti- ...